Hardware IP protection by exploiting IP vendor’s proteogenomic BioMarker as digital watermark during behavioral synthesis - Anirban Sengupta; Nabendu Bhui; Vishal Chourasia (Scientific Reports)
Abstract Handling the threats of intellectual property (IP) piracy and false IP ownership claim, are central from the perspective of IP vendor’ right as well as reliability of system-on-chip (SoC) designs. IP design piracy has become an emergent concern for the digital hardware design community, in the last few years. This paper presents a novel behavioral synthesis based hardware IP Protection methodology that exploits IP vendor’s proteogenomic Bio-marker as digital Watermark (BioW-IPP), for detective countermeasure against IP piracy and quashing false IP ownership claim. The proposed approach is capable of exploiting the IP vendor’s bio-watermark (proteogenomic signature) as secret digital evidence (BW-ID) to generate a robust hardware watermark for embedding into the IP design during behavioral synthesis/high level synthesis (HLS) process. The generated proteogenomic signature bio-watermark is embedded into the register allocation phase of behavioral synthesis (HLS) that ensures negligible design overhead post-embedding. The proposed approach on comparison with prior behavioral synthesis based watermarking techniques achieved greater security in terms of lower probability of coincidence (watermark collision) and higher tamper tolerance, at nominal design overhead.